Carbon Monoxide Poisoning with Classical Neurological Symptoms and CT Findings - Pant, Chiranjibi; Karki, Binod; Shrestha, Biswo; Karki, Parag; Paudel, Raju (Medical Journal of Shree Birendra Hospital, 2016)
Carbon monoxide (CO) is one of the leading causes of accidental poisonings. Mild poisoning produce symptoms like headaches, vertigo and flu like effects, whereas larger exposures can lead to significant toxicity of the central nervous system (CNS) including death. High index of suspicion is thus necessary specially while evaluating collection of such cases in winter months with a careful history taking. Here, we are reporting a case of suspected CO poisoning diagnosed on the basis of history, response to supportive treatment, exclusion of other causes, and classical computer tomographic findings.